Impact of Leadership Patterns by Likert Classification on Job Performance in the Jordanian Ministry of Youth - Sabah, Moaaz Labib Sulaiman (Journal of Economic, Administrative and Legal Sciences, 2017)
The purpose of this study was to investigate the impact of leadership styles: Exploitive Authoritative, Benevolent Authoritative, Consultative and Participative, according to Likert Leadership styles on job performance: work requirements knowledge, the quality of work, the amount of work done and perseverance and trust, in the directorates of The Ministry of Youth in Jordan. A questionnaire is designed to collect the required data, SPSS is used to analyze it, to achieve the objectives of the study, which focuses on identifying the methods and leadership styles used by the Ministry of Youth directors and their impact on the functionality of the staff of its directorates. 100 questionnaires had been distributed on the employees of the Ministry center, 89 of them were valid for analyzing. The study shows that the Benevolent Authoritative leadership style comes first, then the Exploitive Authoritative, followed by the Consultative leadership style, and then the Participative leadership style ranks last. The study also shows that the prevalent management style in the Ministry of Youth in Jordan is a Benevolent Authoritative leadership style. Depending on the answers of the sample, the study shows a high level of functionality of the staff in the Ministry of Youth in Jordan. The study also shows statistically significant relationship at the level of significance (α ≤0.05) between the independent variable, that is each of the leadership patterns on the dependent variable which is the performance in the Ministry of Youth in Jordan. The study recommends several recommendations, including: giving employees the authority to take some of the non-critical daily decisions, improving the communication channels between the manager and his employees, through regular meetings for example. Focusing on the motivating factors and trying to take advantage of the private sector expertise and success in the field of management. Finally, the confirmation to place the right person in the right place for supervisory positions as heads of departments because of its potential impact on job performance and recommended by the study, another recommendation is to repeat the same study but from the manager’s point of view, while this study is from the employees point of view.